2012
DOI: 10.1007/s00280-012-1879-x
|View full text |Cite
|
Sign up to set email alerts
|

AZ64 inhibits TrkB and enhances the efficacy of chemotherapy and local radiation in neuroblastoma xenografts

Abstract: Neuroblastoma is a common pediatric tumor characterized by clinical heterogeneity. Because it is derived from sympathetic neuroblasts, the NTRK family of neurotrophin receptors plays an integral role in neuroblastoma cell survival, growth, and differentiation. Indeed, high expression of NTRK1 is associated with favorable clinical features and outcome, whereas expression of NTRK2 and its ligand, brain-derived neurotrophic factor (BDNF), are associated with unfavorable features and outcome. AZ64 (Astra Zeneca) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…Our results and the previous studies 14,15 provide compelling evidence that the combination of a Trk inhibitor with current cytotoxic therapies will improve treatment efficacy.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our results and the previous studies 14,15 provide compelling evidence that the combination of a Trk inhibitor with current cytotoxic therapies will improve treatment efficacy.…”
Section: Discussionsupporting
confidence: 56%
“…13 Other Trk inhibitors, AZ623 and AZ64, were found to inhibit activation of TrkB in vitro and had a synergistic effect on tumor growth with topotecan in vivo. 14,15 In our current study, we found that while AZD6918 may not be sufficient to inhibit tumor growth or increase mice survival as a single agent at the tested doses (70 mg/kg, 100 mg/ kg), it did increase the sensitivity of TB3 xenograft tumors to etoposide, a topoisomerase II inhibitor that is currently used in the treatment of NB. This result is consistent with the studies of other Trk inhibitors Lestaurtinib or AZ623 and AZ64.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…90 There are small molecule inhibitors available for the neurotrophin receptors. 91,92 AZ64 is an active, orally available, small molecule kinase inhibitor with nanomolar potency against all 3 NTRK receptors shown to inhibit growth of NTRK-expressing neuroblastomas, both in vitro and in vivo in animal models. 91 AZ64 enhances the efficacy of conventional chemotherapy and RT.…”
Section: Integration Of Recent Advances Into Clinical Practicementioning
confidence: 99%